2020
DOI: 10.1021/acsabm.0c00955
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Composite Nanofiber Containing Fish-Scale Extracts

Abstract: A biodegradable composite nanofiber containing polyhydroxyalkanoate (PHA) or modified PHA (MPHA) and treated fish-scale powder (TFSP) was prepared and characterized. The powder (20–80 nm) was prepared by grinding after treating FSP with water, acid, and heat (450 °C) to yield the TFSP. Composite nanofibers (100–500 nm long) of TFSP/PHA and TFSP/MPHA were fabricated by electrospinning using a biaxial feed method. The TFSP, which had a high hydroxyapatite content, was suitable as a filler for composites. The Ca/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Wu et al [ 275 ] reported a biodegradable composite nanofiber consisting of PHA or modified PHA (MPHA) and treated fish scale powder (TFSP). Using grinding, the powder was prepared after the treatment of FSP with water, acid and heat (450 °C) to produce TFSP.…”
Section: Phas’ Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al [ 275 ] reported a biodegradable composite nanofiber consisting of PHA or modified PHA (MPHA) and treated fish scale powder (TFSP). Using grinding, the powder was prepared after the treatment of FSP with water, acid and heat (450 °C) to produce TFSP.…”
Section: Phas’ Modificationsmentioning
confidence: 99%
“…The water contact angle reduced with increasing TFSP content in MPHA/TFSP and PHA/TFSP nanofiber membranes. The study reported that TFSP improved the hydrophilic effect of the PHA/TFSP and MPHA/TFSP nanofiber membranes providing a more suitable environment for cell growth [ 275 ].…”
Section: Phas’ Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SA particle size distribution was determined using a particle size instrument [32]. The SA samples were dispersed in water under ultrasonic agitation for 30 min.…”
Section: Characterizationmentioning
confidence: 99%
“…Collectively, the peaks indicated the presence of protein, implying that all the bio-discs were coated with a similar material. 55 Fig. 5 illustrates the blood grouping assay for various blood groups performed on bio-discs in active comparison to that on a glass slide or a conventional gold standard test-tube method (Fig.…”
Section: Design Of Bio-disc For Blood Grouping Analysismentioning
confidence: 99%